Factors affecting the implementation of a caring model based on patient satisfaction - Abejuela, Alodia Balin. 4 0 16; 5
ABSTRACT. Statement of the Problem. This study aimed to identify the factors affecting in the implementation of a caring model based on patient satisfaction, at Ospital ng Makati. Specifically, it sought to answer to the following question: 1. What is the profile of the respondents in terms of the following: a. Age b. Sex c. Civil Status d. Number of times hospitalized e. Highest educational attainment 2. What is the level of satisfaction of patients exposed to a Caring Model? 3. What are the factors affecting the level of satisfaction after the implementation of a Caring Model? 4. Is there a significant relationship between the patient respondents' profiles and their level of satisfaction. 5. What Caring Program can be developed based on the results of the study? Hypothesis. The null hypothesis raised in this study was tested at 0.05 level of significance. There is no significant relationship between the patient respondents' profiles and their level of satisfaction. The descriptive research was employed in the study to look into the relationship of variables and possible effects of the caring model based on patient satisfaction. A total of sixty three (63) patients from the general wards (excluding Pedia Ward) of Ospital ng Makati considered as respondents of the study. The questionnaire was the major data gathering tool used in the study. However, interview was likewise utilized for patients who have poor eye sights. The data were coded and entered into a data matrix for a statistical treatment using the Statistical Program for social Sciences (SPSS). For the decriptive presentation of the data particularly in dealing with nominal variables such as age, sex, civil status, educational attainment, and number of times hopitalized, the frequency and percentage were used. To determine the relation of the profile variables on the level of patient satisfaction, Pearson r formula was used. Findings. The salient finding of the study are: 1. The profile of the respondents showed that majority of the respondents are aged 26-35 (25.4%) female (60.3%). Married (71.4%) hospitalized 1 to 2 times (60.2%) and has attained secondary education (39.7%) 2. Age, sex civil status, number of times hospitalized, and educational attainment of the respondents have no significant relationship to their level of satisfaction. The obtained coefficient of correlation between the profile variables and the level of satisfaction with nursing care received were very low and negligible. The probability values(please see Table 2) failed to reach the .05 level of significance - profile variables do not relate to the level of respondents' satisfaction on the nursing care received and so the null hypothesis is accepted. 3. The main satisfaction on the nursing care received as a whole is very satisfactory. However, satisfactory were given to: instructions /explanation prior to procedures/operations, proper draping, family participation, changing of bed linens and orientation upon admission. Encouragement to participate in ward activities, daily morning care, and orientation to the environment were, on the other hand rated as unsatisfactory. Conclusions. The findings lead to the following conclusions: 1. There is no significant relationship between the patients' profile variables and their level of satisfaction over nursing care received. 2. The patients are generally very satisfied with the existing Caring Model of Ospital ng Makati. However, there are specific nursing care/services which they find satisfactory and some unsatisfactory, which needs to be improved/emphasized. These include instructions/explanation prior procedures/operations, proper draping, family orientation, changing of bed linens, orientation upon admission (policies and environment), encouragement to participate in ward activities and daily morning care. Furthermore, there will be basis for the development of a Caring Program. 3. A Caring Program has been developed, enhancing the nursing care/services with very satisfactory ratings, improving the satisfactory and unsatisfactory nursing care activities at Ospital ng Makati. Recommendations. The study's findings and conclusions lead to the following recommendations: 1. Implementation of the Caring Program 2. The caring behaviors incorporated in the Caring Program must become an integral part of the culture and philosophy of the organization, including ongoing reminders and incorporation of the caring program into staff development, job description, staff evaluation, plan for provision of care, and documentation on the patient's record. 3. The hospital administrators should provide financial support to sustain the implementation of the Caring Program.
Thesis (M.A.) -- Pamantasan ng Lungsod ng Maynila, Intramuros, Manila, 2002.;A thesis presented to the faculty of Graduate School of Arts, Sciences, Education, and Nursing, Pamantasan ng Lungsod ng Maynila in partial fulfillment of the requirements for the degree of Master of Arts in Nursing.
Keywords: 2 -- 0; 6; 20; 20; 2